Impact of spiritual beliefs and faith-based interventions on diabetes management - Onyishi, Charity Neejide (World J Diabetes, 2021)
Management of diabetes constitutes significant social and economic burdens worldwide. There is a shortage of empirical studies on the management of diabetes and the associated mental health issues through spiritual beliefs and faith-based interventions (FBIs). It is not also clear how spiritual beliefs and FBIs account for the effective management of diabetic conditions. This article discusses the impact of spiritual beliefs and FBIs in the management of diabetes, from relationship and efficacy studies that report outcomes from experimental procedures of related interventions. The majority of the relationship studies showed positive relationships, while efficacy studies showed a high efficacy of interventions in faith-based approaches. However, none of the studies clearly reported the mechanisms of change or modality of operation in a FBI that can serve as a model across culture and context. Possible mechanisms of change were discussed for further development of a standard faith-based model, and finally, suggestions for future research were also highlighted by the authors.